Main objectives of mental education - Ochilova Nigora Ruzimuratovna (Indonesian Journal of Innovation Studies, 2019)
The relevance of this problem lies in the fact that mental education is an important and at the same time the most difficult section of work in the development of the child, the development of the child occurs both in the course of communication with an adult, playing with pears, and in the process of systematic learning. Themost important role in this is played by this process of mental education carried out in the classroom. The mental upbringing of the child appears not only as the mastery of knowledge and ways of mental activity, but also as the formation of certain personality traits.